2019
DOI: 10.1136/heartjnl-2018-314246
|View full text |Cite
|
Sign up to set email alerts
|

Calculated plasma volume status and outcomes in patients undergoing coronary bypass graft surgery

Abstract: ObjectivesCongestion is associated with worse outcomes in critically ill surgical patients but can be difficult to quantify noninvasively. We hypothesised that plasma volume status (PVS), estimated preoperatively using a validated formula that enumerates percentage change from ideal plasma volume (PV), would provide incremental prognostic utility after coronary artery bypass graft (CABG) surgery.MethodsIn this retrospective cohort study, patients who underwent CABG surgery (1999–2010) were identified from a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 25 publications
(9 reference statements)
4
40
1
Order By: Relevance
“…Taking these results into consideration, PVS could be a useful predictor of poor clinical outcome in patients with heart failure independently of ejection fraction. Annette et al reported that PVS greater than -5.6% is associated with adverse inpatient outcomes such as in-hospital death, postoperative complications and prolonged hospitalization in patients undergoing coronary bypass graft surgery [ 15 ]. Interestingly, their cut-off value for the absence of adverse outcomes was -5.6%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking these results into consideration, PVS could be a useful predictor of poor clinical outcome in patients with heart failure independently of ejection fraction. Annette et al reported that PVS greater than -5.6% is associated with adverse inpatient outcomes such as in-hospital death, postoperative complications and prolonged hospitalization in patients undergoing coronary bypass graft surgery [ 15 ]. Interestingly, their cut-off value for the absence of adverse outcomes was -5.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Actual PV (aPV), ideal PV (iPV), and PVS were calculated by the following equations: aPV = (1-hematocrit)×[a+(b×weight (kg))] where hematocrit is a fraction (Men: a = 1530 and b = 41; women, a = 864 and b = 47.9); iPV = c×weight (kg) where c = 39 in men and c = 40 in women; and PVS = [(aPV-iPV)/iPV]×100% [14,15,18]. Normal range of PVS has not been defined yet.…”
Section: Definition Of Pvsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma volume status (PVS) as a surrogate parameter of congestion is known to directly correlate with increased mortality in patients with stable CHF and can be calculated using only three variables that are readily available for every patient undergoing cardiac surgery (hematocrit, bodyweight and gender) [ 6 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has demonstrated that plasma volume status (PVS) can be calculated easily based on the patients’ weight, gender and hematocrit [ 7 ]. Furthermore, an elevated PVS is known to directly correlate with increased mortality in patients with stable CHF, and has been applied for risk stratification in patients undergoing coronary artery bypass graft surgery or transcatheter aortic valve replacement [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%